Experimental testing on ductile-iron joint panels for high-stiffness segmental joints of deep-buried drainage shield tunnels. (May 2019) - Zhou, Long; Zhu, He-hua; Yan, Zhi-guo; Shen, Yi; Meng, Han; Guan, Lin-xing; Wen, Zhu-yin
Highlights: An experimental method which can reveal the ultimate state of ductile-iron joint panels (DIJPs) is presented. The failure mode of DIJP and its anchor bars is pointed out. The difference between the characteristics of DIJPs in tensile test and that in bending test is presented. Experimental dataset provides a comprehensive basis for design. Abstract: Because of the large earth pressure and high inner water pressure, high-stiffness segmental joints with ductile-iron joint panels (DIJPs) are needed to improve the bearing capacity of segmental joints for deep-buried drainage shield tunnels. DIJPs are always mounted in high-stiffness segmental joints to restrain deformation and reduce the joint rotation angle, thus improving the bearing capacity of segmental joints. Full-scale tensile experiments on the performance of DIJPs with different structural styles, in terms of deformation characteristic, anchorage property, and failure mode, were carried out to evaluate the applicability of DIJPs for deep-buried drainage shield tunnels. The test results show that bending deflection appears in DIJPs if the flexural rigidity of DIJPs is insufficient, which will cause bending-tensile failure for the DIJP anchor bars. The failure position is in the weak interface: the screw thread position of the anchor bars, which is the connection position between the anchor bars and DIJPs; connecting the anchor bars with the main reinforcing bars by stirrups or filling the hand hole can restrain the bending deflection of the DIJP and improve the bearing capacity of the anchor bars. When the anchor bars are connected with the main reinforcing bars, the deformation of the DIJP decreases by 5.6%, and the bearing capacity of the anchor bars increases by 31.1%; further, if the hand hole are filled with cement, the deformation of the DIJP decreases by 22.2% and the bearing capacity of the anchor bars increases by 34.1%. Considering the failure modes of the specimens, it is believed that increasing the flexural rigidity of the DIJP and improving the connection performance between the DIJP and anchor bars can improve the behavior of the DIJP and anchor bars.